Surgical Treatment of Cerebral cavernous Malformations: Report of 6 Cases and pertinent Literature review - Sharma, Gopal Raman; Karki, Prasanna; Joshi, Sumit; Shah, Damber Bikram; Paudel, Prakash; Gyawali, Bidhan; Pokharel, Baburam; Panth, Rajesh (Nepal Mediciti Medical Journal, 2023)
Cerebral cavernous Malformation (CCM) is a rare neurovascular malformation accounting 0.5% to 4% of all intracranial vascular malformations. People harboring CCM may be symptomatic or may present with seizure, hemorrhage or progressive neurological deficit. Asymptomatic CCM needs no treatment. The symptomatic CCM may or may not require intervention. The best treatment for symptomatic CCM is microsurgical excision. Over a period of five years we have been managing I2 patients with CCM, and out of them 6 patients who were symptomatic required microsurgical excision. Here, we discuss these 6 surgically managed patients and appropriate literature related to CCMs would be reviewed.